Doping of Graphene Nanostructure with Iron, Nickel and Zinc as Selective Detector for the Toxic Gas Removal: A Density Functional Theory Study - Mollaamin, Fatemeh; Monajjemi, Majid (MDPI AG, 2023)
In this research, the ability of transition metals (TM)-doped graphene nanosheets to adsorb the toxic gas CO has been investigated. The Langmuir adsorption model was used, with a three-layered ONIOM, using the CAM-B3LYP functional accompanying the LANL2DZ and 6-31+G (d,p) basis sets, and using the Gaussian 16 revision C.01 program, on the complexes of CO adsorbed on (Fe, Ni, Zn)-doped graphene nanosheets. The order of the changes of charge density for the Langmuir adsorption of CO on Fe-doped, Ni-doped, and Zn-doped graphene nanosheets has been investigated. This shows the greatest change of charge density for the Ni-doped graphene nanosheet. However, based on NMR spectroscopy, sharp peaks around the Ni-doped area on the surface of the graphene nanosheet have been observed. In addition, the Ni-doped graphene nanosheet has a large effect on the bond orbitals of C-Ni in the adsorption of CO, having the maximum occupancy. The values of ΔGadso, calculated through IR, showed that ΔGads,CO→ Fe-doped GRo has the highest value, because of a charge density transfer from the oxygen atom in carbon monoxide to the Fe-doped graphene nanosheet. The frontier molecular orbitals, HOMO and LUMO, and the band energy gap accompanying some chemical reactivity parameters, have revealed the attributes of the molecular electrical transport of (Fe, Ni, Zn)-doped graphene nanosheets for the adsorption of CO. As a result, since a CO molecule interacts simultaneously with a Fe, Ni, or Zn atom and the C-C nanosheet, at first it might be separated, as in this state a CO atom constructs a physical bond with the Fe, Ni, or Zn atom, and then the other could be adsorbed chemically on the C-C nanosheet surface. Finally, our results have shown that a considerable amount of charge transfer occurs between CO molecules and TM-doped graphene nanosheets after adsorption, which suggests that TM-doped graphene is more sensitive and selective to the adsorption of CO than a pristine graphene surface.
Keywords: HOMO; LUMO; Organic chemistry; UV-VIS; toxic gases; (Fe, Ni, Zn)-doped/GSs; NMR; CO; QD241-441; ONIOM/DFT; IR